On the “Undying Old Age” of Cleonicus (Matro fr. 7 O.–S.) - Ermolaeva, Elena (Hyperboreus, 2017)
The author defends the manuscript reading γῆρας versus the emendation γῆρυν accepted in recent editions of Athenaeus and Matro of Pitane. The exaggerating hyperbole “undying old age”, which likely means “a very long old age”, seems to be an adaptation of the Homeric formula “undying and not old aged” that ﬁts parodic style better than the ordinary compliment “undying voice” would.